2017
DOI: 10.18632/oncotarget.15290
|View full text |Cite
|
Sign up to set email alerts
|

MiR-204 down-regulation elicited perturbation of a gene target signature common to human cholangiocarcinoma and gastric cancer

Abstract: Background & AimsThere is high need of novel diagnostic and prognostic tools for tumors of the digestive system, such as gastric cancer and cholangiocarcinoma. We recently found that miR-204 was deeply downregulated in gastric cancer tissues. Here we investigated whether this was common to other tumors of the digestive system and whether this elicited a miR-204-dependent gene target signature, diagnostically and therapeutically relevant. Finally, we assessed the contribution of the identified target genes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Although miR‐204‐5p was shown to be decreased in many types of malignancy , the expression level of miR‐204‐5p in HCC tissues has not been reported. To investigate the expression level of miR‐204‐5p in HCC, we analysed the data from TCGA online data set (http://cancergenome.nih.gov/).…”
Section: Resultsmentioning
confidence: 98%
“…Although miR‐204‐5p was shown to be decreased in many types of malignancy , the expression level of miR‐204‐5p in HCC tissues has not been reported. To investigate the expression level of miR‐204‐5p in HCC, we analysed the data from TCGA online data set (http://cancergenome.nih.gov/).…”
Section: Resultsmentioning
confidence: 98%
“…48 It may play a regulatory function in stem cells through targeting the CD44 and NOTCH. 49 miR-34a and miR-10b target/regulate some of stemness genes and EMT factors but with lower correlation to both pathways. The role of both miRNAs in BCSCs has been reported previously in several studies.…”
Section: Discussionmentioning
confidence: 97%
“…MicroRNAs (miRNAs/miRs) are a type of non-coding RNA (18–24 nucleotides in length) that regulate mRNA expression by binding to the 3′untranslated regions (UTR) of target mRNAs ( 3 ). Increasingly, evidence has revealed that miR-204 is downregulated in breast cancer ( 4 ), glioma ( 5 ), gastric cancer ( 6 ) and acute myeloid leukemia ( 7 ). However, to the best of our knowledge, no information is available regarding the function of miR-204 in HNSCC progression.…”
Section: Introductionmentioning
confidence: 99%